2014
DOI: 10.1175/jas-d-14-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

What Drives the Brewer–Dobson Circulation?

Abstract: Recent studies have revealed strong interactions between resolved Rossby wave and parameterized gravity wave driving in stratosphere-resolving atmospheric models. Perturbations to the parameterized wave driving are often compensated by opposite changes in the resolved wave driving, leading to ambiguity in the relative roles of these waves in driving the Brewer–Dobson circulation. Building on previous work, this study identifies three mechanisms for these interactions and explores them in an idealized atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 56 publications
11
68
1
1
Order By: Relevance
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, some studies revealed possible compensation of PW drag of the middle atmospheric circulation by parameterized OGWs in general circulation models (McLandress and McFarlane 1993;Cohen et al 2013Cohen et al , 2014Sigmond and Shepherd 2014;Watson and Gray 2015). Our results show that taking account of OGW parameterization can both decrease or increase wave amplitudes, EP-fluxes, and wave drag of the mean flow depending on the considered PW modes.…”
Section: Discussionmentioning
confidence: 57%
“…The large negative difference observed in the zonal GWF in the mesosphere above the polar night jet (i.e., 0.5-0.05 hPa at 60-80°S and 0.1-0.01 hPa at approximately 50°S) is largely compensated by a positive difference in ∇⋅ F of the same order of magnitude. This may be due to a compensation mechanism between parameterized and resolved waves, as suggested by recent studies (McLandress et al 2012;Cohen et al 2013Cohen et al , 2014Scheffler and Pulido 2015).…”
Section: Modification Of the Resolved Wave Forcingsmentioning
confidence: 75%
“…The uncertainty is particularly large for nonorographic GWs. Furthermore, an acceleration of the BDC of 2.0%-3.2% (decade) 21 is seen across models, but there again exists no consensus on the contributions from different wave types in driving this trend (Butchart et al 2006(Butchart et al , 2010Cohen et al 2014;Abalos et al 2015). The differences in resolved versus gravity wave contributions reflect our poor ability to simulate gravity waves.…”
Section: Introductionmentioning
confidence: 98%